Genotypic characterization of rotavirus strains in children hospitalised for acute diarrhea in Belém, Pará, Brazil, in post-vaccine introduction period - Fecury, P. C. M. S (2014)
Trabalho apresentado no Annals of National Meeting of Virology, XXV.; Mercosur Meeting of Virology, IX., 2014. Ribeirão Preto, São Paulo.